Poor reporting of physical activity and exercise interventions in youth mental health trials: A brief report. Issue 5 (13th September 2020) - Pascoe, Michaela C.; Bailey, Alan P.; Craike, Melinda; Carter, Tim; Patten, Rhiannon K.; Stepto, Nigel K.; Parker, Alexandra G.
Abstract: Aim: To describe the quality and completeness of the description and reporting of physical activity and exercise interventions delivered to young people to promote mental health or treat mental illness. Methods: We conducted a series of scoping reviews identifying 64 controlled trials of physical activity and exercise interventions delivered to young people. We extracted: intervention characteristics, personnel and delivery format, the intensity, duration, frequency and type of physical activity or exercise. Results: There was limited reporting of intervention details across studies; 52% did not provide information to confidently assess intervention intensity, 29% did not state who delivered the intervention, and 44% did not specify the intervention delivery format. Conclusions: We recommend that authors adhere to the CONSORT reporting requirements and its intervention reporting extensions, (a) the Template for Intervention Description and Replication, (b) Consensus for Exercise Reporting Template and (c) as part of this, detail the frequency, intensity, time and type of physical activity recommendations and prescriptions. Without this, future trials are unable to replicate and extend previous work to support or disconfirm existing knowledge, leading to research waste and diminishing translation and implementation potential.